Prevalence, clonal dynamics and clinical impact of TP53 mutations in patients with myelodysplastic syndrome with isolated deletion (5q) treated with lenalidomide: results from a prospective multicenter study of the german MDS study group (GMDS) - Mossner, Maximilian; Jann, Johann-Christoph; Nowak, Daniel; Pressler, Jovita; Obländer, Julia; Fey, Stephanie; Müller, Nadine Zoé; Metzgeroth, Georgia; Weiß, Christel; Hofmann, Wolf-Karsten; Nolte, Florian (Leukemia, 2016)
Prevalence, clonal dynamics and clinical impact of TP53 mutations in patients with myelodysplastic syndrome with isolated deletion (5q) treated with lenalidomide: results from a prospective multicenter study of the german MDS study group (GMDS)